METHOD OF NEURO-FUZZY MODEL SYNTHESIS OF QUANTATIVE DEPENDENCES FOR DIAGNOSTICS AND PREDICTION PROBLEMS SOLVING - Subbotin, S. A. (Radio Electronics, Computer Science, Control, 2010)
The problem of neuro-fuzzy approximator constructing has been solved with the aim to automate the construction of numerical models of quantitative relationships. The neuro-fuzzy network model and method of synthesis are proposed. It allows to build a neuro-fuzzy regression model of approximated dependence with the ability of generalization and subjective evaluation of the result certainty.